Smart Lumini: A Smart Lighting System for Academic Environments Using IOT-Based Open-Source Hardware - González-Amarillo, Carlos Andrés; Cárdenas-García, Cristian Leonardo; Caicedo-Muñoz, Julián Andrés; Mendoza-Moreno, Miguel Angel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Rational energy consumption in large buildings depends on both the users' consumption culture and the management systems implemented. In Colombia, few buildings have an energy management system characterized by its adaptability to the user and with a certain degree of intelligence. Thus, this document describes the summarized research process for the development of an Internet of Things (IoT) system, which has been designed to promote an intelligent lighting service in an academic environment. The IoT system orchestrates a series of sensors, monitoring systems and controlled actions, all based on the principle of making the system functions and consumption records available in real-time, via web services. The devices used are "Things" with improved functionality, becoming "Smart Things" within the IoT paradigm. Methodologically, an experimental process was followed, linking the development of electronic tools, the construction of services, and the development of interfaces for a pleasant user experience. Research contributes to two essential areas: intelligent buildings, through the intelligent adaptation of an environment; and sustainability and eco-innovation, since the system provides appropriate information for environmental education, in terms of real-time energy consumption, that impacts directly on the fair-use culture of a service expensive for the environment.